Closing My Eyes and Remembering My Self: Reflections of a Lesbian Law Professor - Miccio, G. Kristian (Columbia Journal of Gender and Law, 1997)
I know that I am in the right place. The room is stuffy. The portraits of past deans line the wall reminding some of us that we are interlopers. The gaze of the dead mixes with that of the living-staring at a podium inhabited by the newest member of the law school faculty. I am here-ready to teach, to probe my students’ minds, and to allow them to probe mine, as we attempt to make sense out of cases in which rights and wrongs are inscribed on our collective consciousness. I am going to do something today that these first year students could not have anticipated. As part of their orientation class, I am going to teach Bowers v. Hardwick to begin their law school careers, and my first day, with an inquiry into the construction of the legal/political Other. And today, these students will be asked to begin this inquiry by submerging themselves into the identity of Michael Hardwick, a gay man arrested in his bedroom by two Georgia police officers. Today, these students and their teacher will attempt to make sense out of state power aimed at those who love members of their own sex. We start with a careful rendition of the facts. I ask one student, a young man, to tell us how Michael Hardwick came to the attention of the court. As he speaks, I am struck by the catalog of facts: arrested, bedroom, two men, caught, sodomitical embrace, jail term, 20 years. His words hang in the air as he completes this brief assignment. Once again, I am reminded of how tenuous the existence of the sexual outlaw is: how it is constructed by the imposition of the will of those who would relegate us to a legal wasteland, where liberty, privacy, and bodily integrity are illusory and reserved only for those who know how to love Right.